Early phase clinical trials to identify optimal dosing and safety. Issue 5 (14th August 2014) - Cook, Natalie; Hansen, Aaron R.; Siu, Lillian L.; Abdul Razak, Albiruni R.
Abstract : The purpose of early stage clinical trials is to determine the recommended dose and toxicity profile of an investigational agent or multi‐drug combination. Molecularly targeted agents (MTAs) and immunotherapies have distinct toxicities from chemotherapies that are often not dose dependent and can lead to chronic and sometimes unpredictable side effects. Therefore utilizing a dose escalation method that has toxicity based endpoints may not be as appropriate for determination of recommended dose, and alternative parameters such as pharmacokinetic or pharmacodynamic outcomes are potentially appealing options. Approaches to enhance safety and optimize dosing include improved preclinical models and assessment, innovative model based design and dose escalation strategies, patient selection, the use of expansion cohorts and extended toxicity assessments. Tailoring the design of phase I trials by adopting new strategies to address the different properties of MTAs is required to enhance the development of these agents. This review will focus on the limitations to safety and dose determination that have occurred in the development of MTAs and immunotherapies. In addition, strategies are proposed to overcome these challenges to develop phase I trials that can more accurately define the recommended dose and identify adverse events. Highlights: Comprehensive review of optimal safety and dosing in early phase cancer trials. Current strategies, limitations and optimization of phase 1 studies are discussed. Various topics covered, including patient selection, start dose and study designs.